The chemical speciation of potential dermally-absorbed copper-based antiinflamatory drugs - Mkhonta-Gama, Lomkhosi (Department of Chemistry, 2023)
It has been shown that increasing the amount of copper associated with low molecular weight ligands in plasma helps to alleviate the symptoms of rheumatoid arthritis (RA). Four low molecular weight ligands 1, 13-bis(N,N-dimethyl)-5,9-dioxo-7-(N-benzyl)- 1,4, 7,10, 13-pentaazatridecane (BID), its de-N-benzylated derivative (IDA), 1,13- bis(N,N-dimethyl)-5,9-dioxo-7-(N-phenethyl)-1,4, 7, 10, 13-pentaazatridecane (D1VIE) and its non-methylated derivative (EDA) were synthesised and characterised. The stability constants of their complexes with divalent copper, zinc and calcium complexes were determined at 25 °C in 0. 15 mo] dm·3 (Na)[CIJ by glass electrode potentiometry. The stability constants found for the copper complexes indicated that in vitro mobilisation of this metal ion was quite appreciable. UVMS spectroscopy was used to investigate the structures of the different copper (II) solution species. Even though the degree of coordination of the different ligands varied, the coordination trend of the different species of the chemical models was similar as pH was increased from 2 to 11. Molecular mechanics calculations were used to propose the geometry of the solution species based on the strain energy of each of the possible geometries. Out of four possible coordination geometries found, the one with the lowest strain energy was accepted as best representing the chemical systems at hand. To investigate the feasibility of dermal absorption of the copper complexes of these ligands, octanol/water distribution coefficient experiments were performed the pH range 2 to 10.5. The results confirm that charge neutrality of a species is important for tissue solubility. The superoxide radical the superoxide dismutase (SOD)-like activity of the copper complexes of these ligands was investigated. The results showed that the SOD-like activity of the present complex systems was too negligible for them to be considered as plausible SOD mimics.